Analysis of Rice Supplies in Public Corporation BULOG Regional Division of Nusa Tenggara Timur (NTT) - FITRIANI, NUR; YUSUF, RIA PUSPA; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.1, Januari 2014, 2014)
ABSTRACT Analysis of Rice Supplies in Public Corporation BULOG Regional Division of Nusa Tenggara Timur (NTT) Rice is the basic requirements that must be met for humans at all times. BULOG as State Owned Enterprises have a primary duty, which is to undertake logistic staple food quality and maintain food stability. The purpose of this study are to (1) determine rice procurement in BULOG NTT, (2) analyze the inventory system of rice by BULOG NTT focused on the economic order quantity (EOQ), minimum stock, maximum stock, and reorder point, (3) the efficiency cost of rice supplies by BULOG NTT which focused on the actual inventory cost effective inventory costs. The method of analysis used in this experiment is a quantitative and qualitative analysis. The study was conducted at BULOG NTT, which is located on Jl. Palapa No 14 Oebobo, Kupang, Nusa Tenggara Timur. Rice purchasing by BULOG NTT started by making a procurement contract with the contractor. The study found that the economical rice booking is 816,65 ton for once, while the amount of safety stock that must be held by BULOG NTT is 35.731,71 ton and maximum inventory that can be managed is 42.813,65 ton. The total cost incurred by rice supplies by BULOG NTT in 2011 was Rp 664.785.013,15 while the analysis of the optimal inventory control cost of Rp 661.160.200,24. So there is the cost efficiency of Rp 3.624.813,01.   Keyword: economic order quantity , BULOG, rice procurement
Keywords: economic order quantity, BULOG, rice procurement